Learning Media and Technology: Generation Z and Alpha - Talizaro Tafonao; Sion Saputra; Rosita Suryaningwidi (Indonesian Journal of Instructional Media and Model, 2020)
The purpose of this article is to analyze the learning media and technology in the Z and Alpha generation teaching and learning activities. This study departs from the author's observation of the current condition of teachers, where educators get a difficulty in teaching students of generation Z and Alpha as described in this article. The problems that found by the author are still very diverse, but it should be noted that there is no room for educators to make excuses and do not use technology as a medium of learning. The method that used is a qualitative research method, the author examines Learning Media and Technology: Generation Z and Alpha. The analysis process carried out by the author is to use a variety of reliable literature and electronic sources to support the author's analysis. The results of this study found that this technology media can uniform the perceptions of student learning, smooth interactive, streamline the teaching and learning process, foster positive attitudes in learning and answer the challenges that exist in the digital era. So by finding the answer to this analysis, the gap between educators and students can be resolved properly.